An Inconvenient truth: The need to educate emotionally competent lawyers - Slocum, Robin Wellford (Derecho y Humanidades, 2014)
The dominant presumption within legal education, that we can teach students to “think like lawyers” with a nearly singular focus on training the analytical mind, is a fiction based on a 19th Century understanding of the human brain that is inherently flawed. Modern neuroscience reveals that the ideal of a dispassionate analytical mind untainted by emotions and personal biases is a fallacy. Nonetheless, this fallacy has spawned an equally faulty premise that still dominates legal education today - that we can train students to be effective lawyers by virtually ignoring students’ emotions and by marginalizing the development of the emotional competencies. These presumptions impose a significant cost on our students and on the legal profession. By marginalizing the importance of emotional competence, we ill-prepare our students to work effectively with the complex interpersonal legal problems they will encounter in the practice of law. As troubling, by dismissing emotions as irrelevant to legal thinking, we ignore that which has true meaning to students – their emotional compass and values. By doing so, we systematically strip students of what is actually meaningful to them as people and ill-prepare them to develop a professional identity that can guide them in their professional careers. This article describes four basic domains of emotional competency that are demanded by the practice of law and reflects on some of the costs we incur by continuing to marginalize emotional competency training in the law school curriculum. The article concludes by offering suggestions for incorporating emotional competency training into the law school curriculum. These ideas range from relatively minor shifts in emphasis in doctrinal and lawyering skills classes to the addition of courses focused exclusively on developing the emotional competencies that are required skill-sets in modern legal practice.